Evaluating Islamic Stock Portfolio Weighting Method: Application Of Global Minimum Variance In Indonesia Islamic Stock Market - Arienka Prilitaningtyas; Taufik Faturohman (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Investing in stocks can be a smart alternative to saving money in a bank or keeping cash on hand due to the negative impact of inflation. It offers various advantages, such as generating income and safeguarding wealth against inflation. Investing in stocks comes with risks, which can be mitigated through strategic portfolio construction. Multiple methods exist for portfolio weighting, one of the popular portfolio weighting methods is Global Minimum Variance (GMV) by Markowitz (1952). This research aims to provide evidence about the performance of the GMV Method for Islamic retail investors using the Jakarta Islamic Index as the investment universe. The study analyzes the out-of-sample performance of GMV compared to Benchmark Indexes, which are IHSG, LQ45, ISSI, and JII. The finding of this study provides that constructing an Islamic stock portfolio using GMV help historically able to help the investor to gain a better return compared to ISSI, LQ45, and JII in the overall observation period and earned better returns compared to all benchmark indexes after the Covid-19 Period. Global Minimum Variance also helps the investor to gain better risk-adjusted return compared to ISSI and JII in the overall observation period and after the Covid-19 Period. Therefore, the retail investor could use GMV to construct their Islamic Portfolio to gain better returns than the market.